Overcoming the false-minima problem in direct methods: structure determination of the packaging enzyme P4 from bacteriophage phi13. - Meier, C; Mancini, E; Bamford, D; Walsh, M; Stuart, D; Grimes, J (2005)
The problems encountered during the phasing and structure determination of the packaging enzyme P4 from bacteriophage phi13 using the anomalous signal from selenium in a single-wavelength anomalous dispersion experiment (SAD) are described. The oligomeric state of P4 in the virus is a hexamer (with sixfold rotational symmetry) and it crystallizes in space group C2, with four hexamers in the crystallographic asymmetric unit. Current state-of-the-art ab initio phasing software yielded solutions consisting of 96 atoms arranged as sixfold symmetric clusters of Se atoms. However, although these solutions showed high correlation coefficients indicative that the substructure had been solved, the resulting phases produced uninterpretable electron-density maps. Only after further analysis were correct solutions found (also of 96 atoms), leading to the eventual identification of the positions of 120 Se atoms. Here, it is demonstrated how the difficulties in finding a correct phase solution arise from an intricate false-minima problem.